Studying for what? The (de)valuation of high school in the speech of three generations - Coutrim, Rosa Maria da Exaltação; Ferreira, Fernanda Moreira; Lebourg, Elodia Honse (Revista Eletrônica de Educação, 2016)
<!--[if gte mso 9]> <![endif]--> As the result of a research done in Mariana, a town in Minas Gerais, Brazil, we investigated the representations of school made by three generations of the same family, i.e., grandparents, parents and grandchildren. Based on a qualitative study, questionnaires were filled in by ninety-six students graduating from high school, from both sexes, in two public schools of Mariana, who live with their parents and grandparents. Five students’ parents and grandparents were selected based on the questionnaire analysis about generational relationships, in order to know the changes throughout the years in the relationship, professional and training expectations for the young people. Among other things, it was observed that school is an institution valued by the family, mainly because it is seen as an effective way to get a good job, although there are differences on the view of the school role between different generations of the same family. Parents consider that the focus is on the individual, i.e., the scholar’s and professional success are considered merit of the student, who must have interest and determination to accomplish their goals. Grandparents consider school the center of education and the largest responsible for the performance of a student in their scholar and professional life. Keywords: Family-school relationship. Generations. High school. <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->